PROTEASE FROM BACILLUS SP. AS A DEGRADING CHICKEN FEATHER FOR PRODUCING FEATHER MEAL - Setyahadi., dkk, Siswa (BPPT)
Chicken feathers are a significant source of protein for livestock because ofhigh protein content and contain large amounts of cystine, glycine, arginine, and phenylalanine. Chicken feathers are not hydrolyzed, it is very difficult to digest by nonruminant animals because they contain high keratin. Hydrolyzed chicken feathers are not very difficult to digest by nonruminant animals because they contain high keratin. Raw chicken feathers must be hydrolyzed to be used as a feed ingredient for nonruminant species. Processing through bio-fermentation of chicken feathers would lead to overhaul the structure of the network, termination of disulfide bonds,hydrogen bonds and decreased levels of keratin. One of the processing of chicken feathers into feather meal is to utilize the specific proteases that degrade keratin. Bacillus sp. which has been isolated from Kawah Putih crater, Ciwidey, Bandung is a protease-producing bacterium. Fermentation using a medium containing: 2.8% (w/ v) glucose, 0.5% (w / v) urea and 0.005% (w / v) yeast extract with the conditions of the process carried out at pH 7.5; temperature 37 0C; shaker incubator 150 rpm will produce protease with the activity of 121 U / ml and prote in content 6.65 mg /ml in 36 hours. Hydrolysis of chicken feather needs to be pepsin digestibility tested to ensure that it has been processed correctly. Chicken feathers was obtained from slaughterhouses in Bogor. Pepsin digestibility of feather meal after hydrolyzed by proteases from Bacillus sp. is 67.4%.Keywords: feather meal, protease, fermentation, Bacillus sp.